2016
DOI: 10.1051/kmae/2015039
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of the infection of juvenile Atlantic salmon with glochidia of the freshwater pearl mussel in rivers of Northwest Russia

Abstract: -The decline of freshwater pearl mussel (Margaritifera margaritifera L.) populations is globally well documented, but there is a lack of knowledge concerning the status of the species and its interaction with host fishes in the rivers of the White and Baltic Seas. This study aimed to identify the host fish of pearl mussel in four rivers of Karelia (Northwest Russia), to analyse the duration of the parasitic phase, and the susceptibility of fish hosts to the infestation. Juvenile sea-migrating and land-locked A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…However, Ieshko et al. () recently found that land‐locked Lake Ladoga (Baltic Sea drainage) salmon were hosts for FPM in a Russian river, but they did not find any brown trout for host comparison. In Norway, FPM populations parasitising only brown trout or salmon have been found in field surveys throughout the country (Karlsson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Ieshko et al. () recently found that land‐locked Lake Ladoga (Baltic Sea drainage) salmon were hosts for FPM in a Russian river, but they did not find any brown trout for host comparison. In Norway, FPM populations parasitising only brown trout or salmon have been found in field surveys throughout the country (Karlsson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This artefact may occur during fixation in well-developed larvae due to the high osmolarity of the fixative and the low diffusion coefficient of the periostracum, similar to other hard tissues, such as cartilage, eye and certain fish tissues (Margo & Lee, 1995;Nassar et al, 2015;Speilberg, Evensen, Bratberg & Skjerve, 1993). Therefore, an accurate evaluation of the integrity of parasite periostracum and internal structures is essential to distinguish this artefact from non-viable glochidia with altered morphology (Ieshko et al, 2016;Treasurer & Turnbull, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One apparent explanation for the incomplete knowledge is the occurrence of FPM in oligotrophic waters that are close to their natural state, meaning that many of the remaining populations are located in remote areas far from human civilization (see e.g. Ostrovsky and Popov 2011, Oulasvirta 2011, Varandas et al 2013, Ieshko et al 2016. Therefore, unexplored rivers and streams in such areas may harbour more unknown FPM populations vulnerable to possible environmental operations by man.…”
Section: Mapping the Occurrence Of The Freshwater Pearl Musselmentioning
confidence: 99%
“…on the western coastline of the Baltic Sea, is known to exclusively parasitize salmon. However, in a Russian river, land-locked salmon from Lake Ladoga (Baltic Sea drainage) was recently found to serve as host for FPM, but the suitability of brown trout as FPM hosts in that river is unknown (Ieshko et al 2016). Outside the Baltic area, Hastie and Young (2001) observed higher infectivity of FPM in salmon than in brown trout in several Scottish rivers, and Karlsson et al (2014) found many Norwegian FPM populations to be exclusively adapted to use only either salmon or brown trout as their host.…”
Section: Margaritifera Hosts (I)mentioning
confidence: 99%